Phenotypical and Molecular Characterization of Acinetobacter baumannii Isolated from Hospitalized Patients During the COVID-19 Pandemic in Brazil - Paula Araujo de Souza; Milena Cristina Nunes dos Santos; Rebeca Vitória da Silva Lage de Miranda; Luciana Veloso da Costa; Raphael Paiva Paschoal da Silva; Cátia Aparecida Chaia de Miranda; Greice Maria Silva da Conceição; Stephen James Forsythe; Maria Helena Simões Villas Bôas; Marcelo Luiz Lima Brandão (Life)
The goal of the present study was to analyze Acinetobacter baumannii strains isolated from hospitalized patients in the period of the COVID-19 pandemic by phenotypic and molecular methods and evaluate their antimicrobial resistance patterns and biofilm production. Forty-seven strains were isolated in 2021–2022 from a hospital in Brazil, and were identified by VITEK®2, MALDI-TOF/MS (VITEK MS® and MALDI Biotyper®), and 16S rRNA sequencing. Fourier-transform infrared (FTIR) spectroscopy was applied for typing and antimicrobial susceptibility testing (AST). In addition, biofilm formation and disinfectant tolerance tests were used. All methods accurately identified all the A. baumannii strains. FTIR typing identified 23 different profiles and 11 clusters, as well as differentiated between the strains from patients with and without COVID-19. Most strains exhibited resistance to the drugs tested, 91.5% of the strains were classified as XDR, 6.4% of the strains were MDR and only 1 strain was classified as non-MDR. Over half of the strains (n = 27, 57.4%) produced biofilms on polystyrene. Sodium hypochlorite (1.0%/15 min) was the best option for effective disinfection. Overall, this study will lay the foundation for further research on effective cleaning protocols for the eradication of A. baumannii biofilms, as well as the use of FTIR for pathogen surveillance in healthcare settings.